Nonzero-sum submodular monotone-follower games: Existence and approximation of Nash equilibria - Jodi Dianetti; Giorgio Ferrari (Bielefeld University, Center for Mathematical Economics (IMW), 2019)
We consider a class of N-player stochastic games of multi-dimensional singular control, in which each player faces a minimization problem of monotone-follower type with submodular costs. We call these games monotone-follower games. In a not necessarily Markovian setting, we establish the existence of Nash equilibria. Moreover, we introduce a sequence of approximating games by restricting, for each n 2 N, the players' admissible strategies to the set of Lipschitz processes with Lipschitz constant bounded by n. We prove that, for each n 2 N, there exists a Nash equilibrium of the approximating game and that the sequence of Nash equilibria converges, in the Meyer-Zheng sense, to a weak (distributional) Nash equilibrium of the original game of singular control. As a byproduct, such a convergence also provides approximation results of the equilibrium values across the two classes of games. We finally show how our results can be employed to prove existence of open-loop Nash equilibria in an N-player stochastic differential game with singular controls, and we propose an algorithm to determine a Nash equilibrium for the monotone-follower game.
urn:nbn:de:0070-pub-29329948
Keywords: 330; nonzero-sum games; singular control; submodular games; Meyer-Zheng topology; maximum principle; Nash equilibrium; stochastic differential games; monotone-follower problem